Validation of the diagnostic utility of hand scintigraphic findings for detecting osteoarthritis in adults - Domínguez Alvarado, Gonzalo Andrés; Diaz Contreras , Indira Eliana; Morales Avellaneda, Tatiana; Saaibi , Diego Luis; Serrano Gomez , Sergio Eduardo; Serrano Baez, Gustavo Adolfo; Martinez Ramirez , Gustavo adolfo; Cifuentes Lopez, Jhoan Sebastian; Rendon Valencia , Carlos Andres (Revista Médica de Risaralda, 2025)
Introduction: Osteoarthritis (OA) is a prevalent condition affecting individuals, particularly in the hands, resulting in pain and functional limitations. Despite its high prevalence, understanding its etiology and diagnosis remains challenging, especially in aging populations. Methods: During the year 2023, a longitudinal study was conducted at a high-complexity center in Santander, Colombia. Its objective was to evaluate the validity of bone scintigraphy (99mTc–MDP) in diagnosing hand OA. Sociodemographic variables, comorbidities, and scintigraphy findings were collected. Statistical analyses included sensitivity, specificity, and predictive values. Results: A total of 192 patients, predominantly women (65.63%), had a prevalence of symptomatic OA of 16.14%. Bone uptake in the joints, especially in the trapeziometacarpal joint, was significantly higher in OA patients compared to those without OA (p < 0.05). The sensitivity of joint uptake for OA diagnosis was 75%, with a specificity of 62%. Significant associations were found between uptake rates and OA diagnosis, particularly in the distal interphalangeal joints of the second and third fingers (p < 0.01). Conclusion: Bone scintigraphy demonstrates potential as a complementary tool for diagnosing hand OA, with significant associations observed between uptake rates and OA diagnosis, especially in specific joints. Despite its limitations, integrating scintigraphy with other diagnostic methods may improve the accuracy of OA assessment, facilitating more targeted treatments and enhancing patient outcomes.